The autonomy of the world and the subjectivity of man in ecotheology - Horowski, Jarosław (Studia Ecologiae et Bioethicae, 2010)
One of the most difficult problems, which is to be solved by contemporary culture, is the ecological problem. It concerns the culture because the hedonistic and consumerist mentality of man plays an important part in it. Biocentrism states that the ecological problem results from traditional Western attitudes to the non-human world based on the belief that humans are the central and most significant entities in the universe. Biocentrism puts forward a teleological argument for the protection of the environment. It indicates that non-human species have inherent value as well and each organism has a purpose and a reason for being, which should be respected. Biocentrism states that the anthropocentric attitude to the non-human world results from the Christian worldview based on the Bible where it is written that God gives man dominion over all creatures. The author analyses the main issues of the Catholic concept of the relationship between human beings and other creatures. He indicates that ecotheology respects the inherent value of non-human creatures because, as the Pastoral Constitution on the Church in the modern world Gaudium et spes says: “all things are endowed with their own stability, truth, goodness, proper laws and order”, but maintains that the purpose of the world is connected with its relationship to God. The author considers also what is the human subjectivity in behaving towards the environment and what is the dependence between the autonomy of the world and the subjectivity of man in ecotheology. In the end, the author comes to the conclusion that according to ecotheology the ecological problem results from the broken relationship between the human and God and in consequence it the broken relationship between the world and God.